The Role of Cardiac Macrophages in Inflammation and Fibrosis after Myocardial Ischemia-Reperfusion - Kaiqin Jin; Zijun Ma; Xiaohe Wang; Chen Gong; Jianlong Sheng; Jun Chen; Shichun Shen (Reviews in Cardiovascular Medicine, 2024)
According to current statistics, the mortality rate of cardiovascular diseases remains high, with coronary artery disease being the primary cause of death. Despite the widespread adoption of percutaneous coronary intervention (PCI) in recent years, which has led to a notable decrease in the mortality rate of myocardial infarction (MI), the pathological cardiac remodeling and heart failure that follow myocardial infarction still pose significant clinical challenges. Myocardial ischemia-reperfusion (MIR) injury represents a complex pathophysiological process, and the involvement of macrophages in this injury has consistently been a subject of significant focus. Following MIR, macrophages infiltrate, engulfing tissue debris and necrotic cells, and secreting pro-inflammatory factors. This initial response is crucial for clearing damaged tissue. Subsequently, the pro-inflammatory macrophages (M1) transition to an anti-inflammatory phenotype (M2), a shift that is essential for myocardial fibrosis and cardiac remodeling. This process is dynamic, complex, and continuous. To enhance understanding of this process, this review elaborates on the classification and functions of macrophages within the heart, covering recent research on signaling pathways involved in myocardial infarction through subsequent MIR injury and fibrosis. The ultimate aim is to reduce MIR injury, foster a conducive environment for cardiac recovery, and improve clinical outcomes for MI patients.